Underdog Entrepreneurs: A Model of Challenge–Based Entrepreneurship - Miller, Danny; Le Breton-Miller, Isabelle (Entrepreneurship Theory and Practice, 2017)
Although there has been abundant research on the positive personality and environmental qualities that stimulate entrepreneurship, we argue that negative personal circumstances of an economic, sociocultural, cognitive, and physical/ emotional nature may have an equally powerful role to play in getting people to become effective entrepreneurs. These challenges create conditions and experiences that motivate particular adaptive requirements which in turn foster outcomes such as work discipline, risk tolerance, social and network skills, and creativity.